The Protective Effect of Health Literacy on Reducing College Students' Stress and Anxiety During the COVID-19 Pandemic - Ying, Yuting; Jing, Chunxia; Zhang, Fan (Frontiers in Psychiatry, 2022)
Background: The coronavirus pandemic (COVID-19) threatens people’s health and well-being all around the world, resulting in increased stress and anxiety. Existing literature has found health literacy has a protective effect on health, and the study has taken a closer look at the effects of health literacy on perceived stress and anxiety among Chinese college students. Methods: With structural questionnaires, a cross-sectional survey was conducted to collect the responses of 1,251 participants from different universities in Hubei and Guangdong, China. Participants’ health literacy and perceived stress and anxiety symptoms were evaluated. Results: Only 11.83% of the participants reported sufficient health literacy. Compared with college students from Hubei, students in Guangdong, and with a major in medicine showed a higher percentage of having sufficient literacy. Moreover, having sufficient health literacy showed a protective effect in reducing the risk of stress (OR=0.14, 95%CI=0.01-0.04; p<.001) and anxiety (OR=0.02,95%CI=0.00-0.61; p <.001). Conclusion: A protective effect of health literacy was found in reducing anxiety and stress among college students, and this effect has remained among students from different majors and locations. However, it is noteworthy that the overall level of health literacy is relatively low among college students, particularly among those from Hubei Province or with non-medical majors. Therefore, more effort should be put into developing health education programs promoting health literacy and mental health on campus.